2020
DOI: 10.3847/1538-3881/ab9305
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Nucleus, Morphology, and Activity of Interstellar Comet 2I/Borisov by Optical and Near-infrared GROWTH, Apache Point, IRTF, ZTF, and Keck Observations

Abstract: We present visible and near-infrared (NIR) photometric and spectroscopic observations of interstellar object (ISO) 2I/Borisov taken from 2019 September 10 to 2019 December 20 using the GROWTH, the Apache Point Observatory Astrophysical Research Consortium 3.5 m, and the NASA Infrared Telescope Facility 3.0 m combined with pre-and postdiscovery observations of 2I obtained by the Zwicky Transient Facility from 2019 March 17 to 2019 May 5. Comparison with imaging of distant solar system comets shows an object ver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 96 publications
5
23
0
Order By: Relevance
“…Nevertheless, even with this upper limit, the size and the mass of 2I/Borisov are in similar ranges of the comets in the solar system [4,6]. We note that our independent observations lead to the results similar to [1,[7][8][9]. It has been reported that the reflectance spectrum of 2I/Borisov is similar to that of comets and D-type asteroids seen in the solar system [10].…”
Section: Resultssupporting
confidence: 62%
“…Nevertheless, even with this upper limit, the size and the mass of 2I/Borisov are in similar ranges of the comets in the solar system [4,6]. We note that our independent observations lead to the results similar to [1,[7][8][9]. It has been reported that the reflectance spectrum of 2I/Borisov is similar to that of comets and D-type asteroids seen in the solar system [10].…”
Section: Resultssupporting
confidence: 62%
“…Containing the original materials from when the solar system first formed, comets provide a unique insight into the distant past of our solar system. The recent discovery of the first interstellar comet 2I/Borisov by amateur astronomer Gennadiy Borisov predictably sparked much excitement and enthusiasm among astronomers and the general public alike (e.g., Bolin et al 2020;Fitzsimmons et al 2019;Guzik et al 2020). Such objects could potentially provide important information on the formation of other stellar systems.…”
Section: Introductionmentioning
confidence: 99%
“…The second interstellar object, 2I/Borisov (hereafter 2I), has had a morphological appearance similar to Solar system comets ever since its discovery (Guzik et al 2020;Bolin et al 2020a). Cometary gas measurements have revealed CO (Bodewits et al 2020;Cordiner et al 2020), and [O I] resulting from photodissociation of H 2 O (McKay et al 2019;Crovisier et al 2019), and the typical visiblewavelength daughter species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The colour and activity of 2I have been revealed to be similar to that of Solar system comets. Visible to near-infrared photometry and spectra of the comet are reddish to neutral suggesting the presence of refractory organics and water-ice common in comets (de León et al 2019;Bolin et al 2020a;Yang et al 2020). Additionally, its activity has been revealed by long-term light curve trending to be driven by supervolatiles such as CO/CO 2 far from the Sun, with the addition of H 2 O-driven activity as the comet crossed inside 3-4 au on its way to a ∼2 au perihelion distance (Bolin et al 2020a;Ye et al 2019;Cremonese et al 2020).…”
Section: Introductionmentioning
confidence: 99%